Large yachts. Strength, weathertightness and watertightness of glazed openings. Glazed opening integrated into adjacent structure (elastically bonded to bulkhead or shell) design criteria, structural support, installation and testing Part 2, (13th August 2020) - British Standards Institution,
No abstract available